2015
DOI: 10.1073/pnas.1508355112
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffusive motion of bacteriophage in mucosal surfaces increases the frequency of bacterial encounters

Abstract: Bacteriophages (phages) defend mucosal surfaces against bacterial infections. However, their complex interactions with their bacterial hosts and with the mucus-covered epithelium remain mostly unexplored. Our previous work demonstrated that T4 phage with Hoc proteins exposed on their capsid adhered to mucin glycoproteins and protected mucus-producing tissue culture cells in vitro. On this basis, we proposed our bacteriophage adherence to mucus (BAM) model of immunity. Here, to test this model, we developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
186
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(200 citation statements)
references
References 49 publications
4
186
0
1
Order By: Relevance
“…[37][38][39][40] Also, recent evidence showed that some bacteriophages bind mucus, which could affect their persistence in the GIT. 41,42 Using CEABAC10 mice, we showed that the cocktail of bacteriophages strongly decreased intestinal colonisation by strain LF82, suggesting that bacteriophages were able to reach the epithelial surface bearing the CEACAM6 receptor of strain LF82. This strong decrease was observed with both CEABAC10 and conventional mice in the absence and presence of antibiotic pressure, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…[37][38][39][40] Also, recent evidence showed that some bacteriophages bind mucus, which could affect their persistence in the GIT. 41,42 Using CEABAC10 mice, we showed that the cocktail of bacteriophages strongly decreased intestinal colonisation by strain LF82, suggesting that bacteriophages were able to reach the epithelial surface bearing the CEACAM6 receptor of strain LF82. This strong decrease was observed with both CEABAC10 and conventional mice in the absence and presence of antibiotic pressure, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Within the scaffolding provided by host-derived nutrients, competition among members of the microbiota may make the community more resilient to external perturbation by pathogens, or chemical agents [54]. Bacteriocins [55], antimicrobials [56], reactive oxygen species [57], and bacteriophage [58, 59] are stresses derived from microbes in the host environment that can structure the competition for nutrients among communties. The production of the bacteriocin coproporphyrin III by a human skin-specific Propionibacterium sp .…”
Section: Microbe-derived Stress Shapes Symbiotic Communitiesmentioning
confidence: 99%
“…Hydrogen peroxide produced by Streptococcus oligofermentans counteracts lactic acid production by Streptococcus mutans in the oral microbiota [57], suggesting that the two species may interact within the diffusive limits of their environment. Bacteriophage-mucin binding interactions have been shown to structure colonization of mucosal layers in the mammalian gut [58, 59], and the accumulation of bacteriophage in sputum or EPS may enhance the protective function of this barrier towards antimicrobials or other chemical stresses [61]. In addition, a functional CRISPR foreign DNA defense system is required for Xenorhabdus nematophila to colonize the gut of its nematode host [62] (Figure 2), suggesting that bacteriophage may be a stressful attribute of the nematode gut microbiota.…”
Section: Microbe-derived Stress Shapes Symbiotic Communitiesmentioning
confidence: 99%
“…Colonization by additional bacterial species and their associated phage continued in the SML until niche space was filled and a community was formed. Mutualistic bacteria continued to protect the metazoan host through competitive exclusion of potential pathogens (Hibbing et al, 2010) while phage provided immune protection as proposed in the bacteriophage adherence to mucus (BAM) model (Barr et al, 2013(Barr et al, , 2015. In the BAM model, phage adhering to mucus provide the host with immune protection against invading pathogens (Figure 1a).…”
Section: Discussionmentioning
confidence: 94%
“…The LCMA secreted mucins from epithelial tissue, generating an SML that selected for bacteria and phage with mucin-binding properties. Phage provided the LCMA with an external microbial selective in which phage bound to mucus via hypervariable domains protect the metazoan host from invading bacteria (BAM) (Barr et al, 2013(Barr et al, , 2015. In addition to attracting bacteria and phage, mucins also increased the rate of contact with eukaryotic viruses resulting in the development of mutualistic symbiosis that provided the LCMA with immune protection.…”
Section: Resultsmentioning
confidence: 99%